Pengembangan Perangkat Subject Specific Pedagogy Ikatan Kimia Berbasis STEM - Kasman, Risqah Amaliah; Danial, Muhammad; Arsyad, Muhammad (Program Pasca Sarjana UNM, 2022)
This study is a development research that aims to produce a STEM-based Chemical Bonds SSP devices. The development model used in this study refers to the 4D development model by Thiagarajan, et al, which consists of the definition stage, design stage, development stage, and dissemination stage. The learning device developed are lesson plan, students’ learning materials, LKPD, and THB. The systematic preparation of each component of the SSP device is in accordance with the standard process in Permendikbud Number 22 of 2016. The learning scenario adopts the Problem Based Learning (PBL) syntax on Chemical Bonds materials. The trial of the SSP device was conductedt UPT SMKN 2 Barru with a total of 35 students. The result of expert validation shows that the developed SSP devices are in very valid category with an average value of 3.50. The developed SSP devices meet the very practical criteria with an average value of 90.44. The increase in learning outcomes as evidenced by class completeness which reached 85.71% indicates that these SSP devices are in effective category. Therefore, it can be concluded that the developed STEM-based SSP device products are valid, practical, and effective.